FORMATIVE-CONSTRUCTIVIST VALENCES OF THE TEACHING PORTFOLIO - Vali ILIE (Universitaria Publishing House, Craiova, 2022)
The portfolio represents a complex assessment tool that includes the relevant outcomes of the students during a learning program. Starting from its role in the academic activity of the students, we aimed in this study to identify the specific aspects of this longitudinal method of assessment and to record, in a constatative research, the way the students relate to the elaboration of the portfolio for the graduation of the psycho-pedagogical module specific to level I, License. The interpretation of their answers to the items of the questionnaire about the relevance and importance of the graduation portfolio is, in our opinion, a starting point in improving the subsequent instructive-educational approaches.